Oxidative Stress and Survival of Leishmania spp.: A Relationship of Inverse Proportionality for Disease Outcome - Souravi Roy; Mayumi Mandal; Moumita Halder; Pijush K. Das; Anindita Ukil (Expert Reviews in Molecular Medicine)
Abstract